Calculation of K Uptake by Two Crops Grown under Field Conditions Using a Mechanistic Model (University of Khartoum Journal of Agricultural Sciences, 2023)
The objective of this study was to compare simulated andactual potassium uptake by two crops, using soil and plant parametersobtained from a field experiment conducted in 2003, in Bavaria, southernGermany. Sugar beet (Beta vulgaris L. cv. Kawetina) and wheat (Triticumaestivum L.cv. Star) were grown on a sandy clay loam in the field. The Ktransport in soil and uptake by the plants were simulated by a mechanisticmodel which encompasses uptake by root hairs as well. A sensitivityanalysis was carried out in an attempt to understand the significance ofsingle soil and plant parameters for nutrient uptake. The simulation modelcalculated only 34 % of the measured sugar beet uptake throughout thegrowing period. The lowest calculated K influx (only 9 % of measuredvalue) corresponded to the period June 24th–July 8th of highest actualuptake. Sensitivity analysis showed that, under low K concentrations, Kconcentration in the soil solution was the most important factorcontrolling K uptake, especially for sugar beet. This indicates that rootsmay have increased the K concentration in soil solution by chemicalmobilization. Research is needed to understand the mechanism by whichthis is achieved.
Keywords: Mechanistic model; rhizosphere; sensitivity analysis; wheat; sugar beet